Development of a STEM-Based Science E-Module to Enhance Students’ Communication and Creativity Skills on Biodiversity Material - Rini Oktavia; Masriani; Sitti Aminah (Postgraduate, University of Mataram, 2025)
His study aims to develop a STEM-based science e-module to enhance seventh-grade students’ communication and creativity skills in biodiversity material at MTs Negeri 1 Palu. The research employed a Research and Development (R&D) method with the ADDIE model, which includes stages of Analysis, Design, Development, Implementation, and Evaluation. Validation was conducted by content and media experts, as well as teachers and students. The developed e-module demonstrated high validity, with scores of 82% from content experts and 76.25% from media experts. Practicality testing also showed strong usability, with 86% approval from teachers and 92% from students. Implementation of the e-module led to significant improvements in student outcomes, increasing communication skills from 62% to 89% (Cohen’s d = 1.99) and creativity from 59% to 93% (Cohen’s d = 1.95). These results indicate that the e-module is not only valid and practical but also effective in enhancing communication and creativity skills, thus supporting the development of 21st-century competencies.